PENGARUH DISIPLIN KERJA DAN PENILAIAN PRESTASI KERJA TERHADAP KINERJA MELALUI KOMPENSASI PEGAWAI SEKRETARIAT DPRD KOTA PROBOLINGGO - Evi Aprilia; Mei Indrawati (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The purpose of this research is to determine the effect of work discipline and work performance assessment on performance through compensation for Probolinggo City DPRD Employee Secretariat. This type of research uses quantitative methods with data analysis using the SmartPLS 3.0 application. The results of the research show that work discipline, work performance assessment, compensation and performance of Probolinggo City DPRD Secretariat Office Employees are in the good category. Work discipline has no influence on the compensation of Probolinggo City DPRD Secretariat Employees. The work performance assessment has no influence on the compensation of the Probolinggo City DPRD Employee Secretariat. Work discipline has no influence on the performance of the Probolinggo City DPRD Employee Secretariat. 5) Work performance assessments have an influence on the performance of the Probolinggo City DPRD Employee Secretariat. Compensation has no influence on the performance of the Probolinggo City DPRD Employee Secretariat. Work discipline has no influence on performance through compensation for Probolinggo City DPRD Secretariat Employees. Job performance assessment has no influence on performance through compensation for Probolinggo City DPRD Secretariat Employees.